Pembuatan Website Dwibahasa untuk Bimbingan Belajar Smart Club - Augustine, Andrea Benitha; Sembiring, Bahtera (English Education:Journal of English Teaching and Research, 2021)
Following the widespread use of the Internet, more businesses are available online to attract more customers and unleash the limits of offline businesses. Not only e-commerces, but websites can be owned by businesses which provide services as what they sell. The reason behind this is that many have found the importance of websites. An example of service businesses is tuition center. This website project is about creating a bilingual website for a tuition center in Bandung. Qualitative methodology was used in collecting the data, and the methods were observation, interview, and library study. This project is aimed to give detailed information, to promote, and to persuade visitors to join the tuition center.